DIET COMPOSITION OF PELAGIC FISH IN THE SOUTHWESTERN ATLANTIC, BRAZIL: AN ISOTOPIC MIXTURES APPROACH - Gorni, Guilherme Rossi; Ribeiro, Maria Lúcia; Goitein, Roberto; Amorim, Alberto F. (Arquivos de Ciências do Mar, 2017)
The purpose of this study is to characterize, through isotopic mixture models (13C and 15N), the diet of pelagic top predators of the Southwestern Atlantic Ocean. Thus, samples of muscular tissue were collected from individuals of the species: Xiphias gladius, Thunnus obesus, Thunnus alalunga, Thunnus albacares, Prionace glauca, Alopias superciliosus and Isurus oxyrinchus. Results indicate the diet of X. gladius is primarily composed by cephalopods (Ommastrephidae squids). A similar pattern is presented by T. alalunga, whose food is also mainly composed by Ommastrephidae squids. T. obesus and T. albacares present similar compositions, but smaller pelagic fish species are important to their diet compositions. A. superciliosus feeds mainly on Scombridae species (T. albacares and T. alalunga). A. superciliosus diet is composed mainly by Scombridae species, differing from that one from P. glauca, whose diet consists of smaller pelagic fish. The use of information in a conjugated way of the predators’ stomach contents as well as the isotopic tissue analyses may be a important step towards a more complete understanding of pelagic food web composition in Southwestern Atlantic Ocean.